Utilization of Purple Sweet Potato (Ipomoea batatas 'Blackie') as Raw Ingredient in Pizza Production - Khosyiati, Nur Evirda; Setiawan, Rizal Justian; Ma'ruf, Khakam; Azizah, Nur; Darmono (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
Indonesia remains highly dependent on wheat imports, reaching 7.39 million tons annually, threatening national food security. Additionally, this heavy reliance on wheat imports can jeopardize economic stability, as wheat prices are controlled by producing countries. Therefore, it is essential to find local food alternatives that can replace wheat, one of which is purple sweet potato (Ipomoea batatas Blackie), which is widely available in Indonesia. This study explores the potential of purple sweet potato as an alternative raw ingredient in pizza production to reduce dependence on wheat imports. The research employs an experimental method with qualitative and quantitative analysis. Pizza was prepared by partially substituting wheat flour with purple sweet potato, followed by an organoleptic test conducted by 20 panellists to evaluate taste, texture, aroma, color, and presentation. The results indicate that purple sweet potato pizza has a balanced nutritional composition, containing 250 kcal of energy, 40g of carbohydrates, 6g of protein, 8g of fat, 3g of fiber, 500IU of vitamin A, and 10mg of vitamin C per 100g. Market response to this product was highly positive, with an average overall score of 4.38 out of 5, indicating good consumer acceptance. The substitution of purple sweet potato in pizza not only enhances nutritional value but also offers a more sustainable local food alternative. This study concludes that this innovation has the potential to be developed within the food industry, support food diversification, and reduce reliance on imported wheat flour.